Perancangan & Implementasi SI Layanan Kesehatan Masyarakat - Iis; Dedy Hermanto (JuSiTik : Jurnal Sistem dan Teknologi Informasi Komunikasi, 2017)
Abstrak—The availability of information to the public by health providers such as Hospitals and the Palang Merah Indonesia is an important issue to be studied and kept in mind as it involves the interests of many people and requires a fast response time. For example the need for inpatient information, physician information, queue number information by the Hospital and information on blood availability by the Palang Merah Indonesia (PMI). The availability of that information is raised by the researcher Good health service is one of the things desired by everyone, especially the health service one of which is the availability of information quickly. Fast and accurate access to information from hospitals and the Palang Merah Indonesia (PMI) is urgently needed by every health care user. In order for this activity to run optimally, web-based information system applications and mobile devices can be one solution. In this study the authors use Rational Unified Process Methodology (RUP), Meotodologi has 4 phases of Inception, Elaboration, Construction and Transition. This study produces information systems that use 2 base application that is web and mobile device, useful to give exact information about existence of room, doctor on duty, stock of blood and queue of patient who will do hospitalization in a hospital. From the results of this study the expected results of each patient gets a fast and good service, and information obtained is accurate and fast information